(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Factors affecting the deposit policy of commercial banks are analyzed in the article. In addition, conclusions, recommendations and suggestions on improving the practice of managing the transformation and liquidity risks that occur when the deposits are diverted to credit operations in the dynamics of interest rates on deposits are given.